2002
DOI: 10.1086/341516
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a Rotating Supermassive Star to a Supermassive Black Hole: Fully Relativistic Simulations

Abstract: We follow the collapse in axisymmetry of a uniformly rotating, supermassive star (SMS) to a supermassive black hole in full general relativity. The initial SMS of arbitrary mass M is marginally unstable to radial collapse and rotates at the mass-shedding limit. The collapse proceeds homologously early on and results in the appearance of an apparent horizon at the center. Although our integration terminates before final equilibrium is achieved, we determine that the final black hole will contain about 90% of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
183
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 25 publications
12
183
0
Order By: Relevance
“…However, a post-Newtonian calculation cannot follow the collapse into the strong-field regime and cannot rigorously address the outcome of the collapse. The fate of a marginally unstable, maximally rotating SMS of arbitrary mass has been investigated numerically in full general relativity by Shibata and Shapiro (2002). They found that the final object is a Kerr-like black hole (spin parameter ≈0.75) containing 90% of the stellar mass.…”
Section: Gas-dynamical Processesmentioning
confidence: 99%
“…However, a post-Newtonian calculation cannot follow the collapse into the strong-field regime and cannot rigorously address the outcome of the collapse. The fate of a marginally unstable, maximally rotating SMS of arbitrary mass has been investigated numerically in full general relativity by Shibata and Shapiro (2002). They found that the final object is a Kerr-like black hole (spin parameter ≈0.75) containing 90% of the stellar mass.…”
Section: Gas-dynamical Processesmentioning
confidence: 99%
“…The particular direct collapse scenario we address here requires the presence of large accretion rates of about ≥ 0.01 − 0.1 M ⊙ /yr (Begelman 2010;Hosokawa et al 2013;Schleicher et al 2013;Ferrara et al 2014). This is because such accretion rates are the main pre-requisite to rapidly build a supermassive star of about 10 4 − 10 5 M ⊙ , which would eventually collapse into a black hole retaining most of the star's mass (Baumgarte & Shapiro 1999;Shibata & Shapiro 2002). These large accretion rates can either be obtained through dynamical processes or thermodynamically, by keeping the gas warm (i.e, with a higher Jeans mass) to avoid fragmentation and star formation.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, situations in which accretion disks with masses comparable to that of the central black hole can be formed. Examples include the collapse of rapidly rotating stars or supermassive stars [25], and neutron star merger (especially when the two neutron stars have unequal masses [2]). In these cases, the spacetime is dynamical and Einstein's equations for the metric must be evolved along with the MHD equations.…”
Section: Introductionmentioning
confidence: 99%